Analisis Penerapan GCG menggunakan Data Time Series BCA dengan Otomasi NVIVO 12 - Hastuti Olivia; Nurluthfiyyah Syarifah Hanun Siregar; Muhammad Razaq Arafi; Zaskia Akhira; Waha Rira Nadirah; Azzahra Innayatussyfa (Bisnis-Net, 2023)
Implementing good corporate governance is the first step in improving a company's performance, performance and reputation which can become a magnet for consumers and increase business progress. However, corporate governance is not managed well in Indonesia, even though good corporate governance can have a significant impact on the company itself and can even support the Indonesian economy. This research aims to look at the implementation of good corporate governance at Bank Central Asia using time series data with NVivo qualitative data analysis. The data used is an overview of Bank Central Asia's financial and corporate governance data obtained from Bank Central Asia's own good corporate governance report database. The research results show that the implementation of Good Corporate Governance (GCG) at BCA has good performance and the bank's rating based on the company's OER/BOPO data is considered very healthy.